Ekstraksi dan Isolasi Bahan Alam Secara Klasik dan Modern - Erwin, Erwin; Fadliannur, Fadliannur; Alimuddin, Alimuddin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Extraction and isolation of bioactive compounds from natural materials is an important process in the pharmaceutical, chemical, and biotechnology industries. This process aims to obtain active compounds from plants, microorganisms, or animals for various applications. Classical extraction has been used for years, while modern methods have developed along with technological advances. This paper discusses the differences between classical and modern methods in the extraction and isolation of natural materials, including techniques, advantages, disadvantages, and fundamental differences between the two. Understanding these methods is important to improve efficiency and sustainability in the process of isolating bioactive compounds. Keywords: Extraction, isolation, natural materials, classical methods, modern methods, bioactive compounds.